Текстиль и органика салтовского времени из Нетайловского могильника - Крупа, Т.Н. (Степи Европы в эпоху средневековья, 2009)
The paper considers new finds of ancient textile and adjoined organics in the burial ground of the Saltov period near Netailovka village. Volchansk region, Kharkov province. It was this unique site where a new technique of extracting material from unearthed burial was adopted for the first time. This technique implies that the ground which potentially contains any archaeological organics is cut out in a monolith piece. The bulk of the material obtained using this method of excavations of the burial ground in 2003-2004 and 2006 permits us to raise the question about the sources of delivery of abundant quantity of silk into the territory of North-Eastern Khazaria during the 8th-10th centuries. It can be asserted that the Seversky Donets medieval commercial waterway played an important role in the trade of Chinese silk in Khazaria. This is confirmed by the finds from Netailovka burial ground.